An implantable telemetry platform system for in vivo monitoring of physiological parameters. - Valdastri, P. (IEEE Transactions on information technology in biomedicine)
This paper describes a microcontroller-based multichannel telemetry system, suitable for in vivo monitoring of physiological parameters. The device can digitalize and transmit up to three analog signals coming from different sensors. The telemetry transmission is obtained by using a carrier frequency of 433.92 MHz and an amplitude-shift keying modulation. The signal data rate is 13 kb/s per channel. The digital microcontroller provides good flexibility and interesting performance, such as the threshold monitoring, the transmission error detection, and a low power consumption, thanks to the implementation of a sleep mode. The small overall size (less than 1 cm3), the power density compatible with current regulations for the design of implantable devices, and the dedicated packaging make the system suitable for in vivo monitoring in humans. The design, fabrication, operation, packaging, and performance of the system are described in this paper. An in vivo pressure monitoring case study is described as well.